OBSESSIVE COMPULSIVE DISORDER TOKOH AOYAMA DALAM ANIME KEPPEKI DANSHI! AOYAMA-KUN KARYA KAZUYA ICHIKAWA - Fhansi Miyoki Rahena Santi; I Made Budiana; Ni Luh Putu Ari Sulastri (Widyadari, 2025)
Mental disorder in the character Aoyama is the main focus of the study titled “Obsessive Compulsive Disorder of Aoyama in the Anime Keppeki Danshi! Aoyama-kun by Kazuya Ichikawa.” This research aims to identify the form of Obsessive Compulsive Disorder (OCD) and its impact on the character's social life. Theories used include Sigmund Freud's psychoanalysis, anxiety disorder theory by Nevid, Rathus, and Greene, and Melvin Seeman's social alienation theory. This qualitative descriptive analysis uses informal presentation methods. The findings show that Aoyama, a high school soccer player, displays OCD symptoms such as washer and cleaner and repeater, which are influenced by the dominance of id, ego, and superego. These behaviors result in social impacts including loss of self-control, lack of social meaning, absence of norms in interaction, social isolation, and individual alienation. The study reflects how psychological disorders affect social relationships in daily life